Anotasi Putusan Pengadilan Tata Usaha Negara Nomor 110/G/KI/2019/PTUN.BDG dan Implikasinya terhadap Pejabat Tata Usaha Negara - Darusman, Hildan (Lembaga Yasin AlSys, 2022)
This research is to examine the basis for the consideration of the panel of judges at the Bandung State Administrative Court, which has decided on a dispute application. Information about the inspectorate audit report as information that is open to the general public. Disclosure of public information is one of the important elements for the realization of good governance or Good Governance in the administration of government. The purpose of this paper is the first to describe the judge's considerations in the decision of the Bandung State Administrative Court in Deciding Case Number: 110/G/KI/2019/PTUN.BDG Regarding Public Information Disclosure Disputes, the second is sanctions against State Administrative Officials who do not implement decision No.110/G/KI/2019/PTUN.BDG. This research is juridical normative oriented to legal analysis of the reality of the application of legal norms contained in various laws on public information disclosure in the decisions of the Bandung State Administrative Court. Sources of legal materials are based on primary legal materials and secondary legal materials. Primary legal materials are in the form of various decisions of the State Administrative Court and secondary legal materials.